Persepsi Mahasiswa FKES UDINUS terkait Hoax Covid-19 - Haikal Haikal; Ratih Pramitasari; Jaka Prasetya; Agus Perry Kusuma (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Hoax news or information relating to Covid-19 affects the obstruction of efforts to contain the Covid-19 pandemic. This research is a descriptive study because it provides an overview or description of students' perceptions in news related to the covid-19 hoax. The results that obtained information from this study were 208 respondents or 54% of the total respondents considered hoaxes as information with no known truth, 168 respondents or 44% revealed that hoaxes related to Covid-19 were most often found or said to be hoaxes as a global elite conspiracy, 223 respondents or 58% of the total respondents received hoaxes related to Covid-19 through writing and pictures, 162 respondents or 42% of the total respondents considered that steps that could be taken to overcome the spread of hoaxes related to Covid-19 were cross-checking or clarifying first , 317 respondents or 83% thought that each party was responsible for overcoming the spread of hoaxes related to Covid-19 and 150 respondents or 39% of the total analysis that information on social media had a negative influence. The conclusion in this study is that health hoaxes can not only cause disputes like political hoaxes, but can also cause the loss of a person's life. Digital literacy skills will be able to provide hoax. Critical and analytical thinking is also an asset to prevent the spread of covid-19 related to hoaxes